Knowledge Regarding Pregnancy Induced Hypertension among Pregnant Women Attending in a Tertiary Hospital - Basnet, Sreejana; Bhattarai, Saraswoti Kumari Gautam; Panta, Ganga (Journal of Nursing Education of Nepal, 2023)
Introduction: Pregnancy induced hypertension is a leading cause of maternal and fetal morbidity and mortality worldwide. It poses risks to both the mother and the baby, associated with premature delivery, growth limitations, placental abruption and even maternal mortality. Therefore, the study aims to find out the level of knowledge regarding pregnancy induced hypertension among pregnant women attending in tertiary hospital. Methods: A descriptive cross sectional study design with a purposive sampling technique was used to assess the knowledge regarding pregnancy induced hypertension among pregnant women attending antenatal outpatient department, Tribhuvan University Teaching Hospital. The total sample size was 195. Face to face interview technique was used to collect the data. Analysis was done by using the Statistical Package for Social Science 16 version using descriptive statistics and inferential statistical test (chi-square test and fisher’s exact test). Results: Less than one fifth (17.9%) of respondents had adequate level of knowledge, less than half (47.7%) had moderately adequate knowledge level and more one third (34.4%) had inadequate knowledge level regarding pregnancy induced hypertension. The level of knowledge was significantly associated with occupation (p=0.019) and source of information (p= 0.001). Conclusion: This study revealed that only one fifth pregnant women had adequate knowledge on pregnancy induced hypertension; and knowledge is significantly associated with occupation. Therefore, awareness raising program need to be conducted in the antenatal clinic to increase the knowledge level of majority of pregnant women. DOI: https://doi.org/10.62143/86m16g41